PENGARUH ORIENTASI PASAR, INOVASI PRODUK DAN JARINGAN USAHA TERHADAP KEUNGGULAN BERSAING (STUDI KASUS PADA IKM ROTAN DI BALEARJOSARI KECAMATAN BLIMBING KOTA MALANG) - sasvita diana sari; Siti Saroh; daris zunaida (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2020)
IKM Rattan is a small and medium industry engaged in rattan craftsmen. The purpose of this study is to determine the significant influence between market orientation, product innovation and business networks on competitive advantage partially and simultaneously. This research uses quantitative research methods. The sample in this study were 41 SMIs, and the data analysis technique used multiple linear regression analysis. Research results Market orientation and product innovation do not have a significant effect on competitive advantage partially, business networks have a significant effect on competitive advantage partially and market orientation, product innovation and business networks have a significant effect on competitive advantage simultaneously.